Automated vehicle lateral guidance using multi-PID steering control and look-ahead point reference. (8th October 2021) - Monot, Nolwenn; Moreau, Xavier; Benine-Neto, André; Rizzo, Audrey; Aioun, François
In this paper, a complete analysis of the influence of a look-ahead distance and the longitudinal vehicle velocity on the vehicle lateral dynamics is made in order to choose an adequate control strategy for lane keeping. Since the longitudinal velocity can be easily and accurately measured, a gain scheduling strategy based on the longitudinal velocity is employed in the design of a robust multi-PID for the lateral control. Implemented onboard of a C4 Picasso prototype vehicle, the proposed controller showed promising results at variable speed and a satisfactory accuracy for lateral positioning.